국내 갈락토스혈증 아동의 식행동 및 영양섭취 실태에 관한 연구 - 서혜지; 정예승; 김유리; 오지은; Hye Ji Seo; Yeseung Jeong; Yuri Kim; Jieun Oh (Journal of the Korean Society of Food Culture, 2022)
Galactosemia is a rare, hereditary metabolic disorder caused by the accumulation of galactose and its metabolites in the body due to a lack of enzymes that convert galactose to glucose. This study aimed to investigate the dietary behaviors and nutritional statuses of patients with galactosemia and to provide basic information on the development of nutrition education programs to improve quality of dietary life. A survey was conducted on 13 parents of (<11 years of age) children with galactosemia and 26 parents of (<11 years of age) children without galactosemia. Mean body mass index was greater for school-age children with galactosemia (18.77 kg/m2) than for corresponding normal children (16.55 kg/m2). Underweight and obesity rates of children with galactosemia were greater than those of children without galactosemia. In addition, children with galactosemia had a higher food neophobia rate and thus consumed less food. Normal children exhibited a greater range of food preferences than those with galactosemia, especially for milk and dairy products (p= .001) and fats and sweets (p= .04). Reliable food databases and appropriate dietary recommendations are required to ensure the proper growth of children with galactosemia.